Genetic structure of Dicksonia sellowiana Hook. (Dicksoniaceae) reveals clinal distribution along the latitudinal gradient of the Atlantic Forest - Fagundes,Bruna Saviatto (2020)
ABSTRACT Dicksonia sellowiana is the only species of the genus occurring in Brazil. Its distribution is restricted to humid areas of the Atlantic Forest biome. The distribution pattern of biodiversity in this biome is known to have been influenced by historical and environmental factors, although the pattern for ferns remains unknown. This study is first to describe the genetic structure of D. sellowiana along the latitudinal gradient of the Atlantic Forest biome. We use microsatellite markers to estimate genetic diversity and structure for 267 individuals representing 14 populations of D. sellowiana from the Atlantic Forest. The results (Ho, He, Fst, Fis, distance genetic) support the hypothesis of a pattern of biodiversity discontinuity. We found greater genetic variability in populations located in regions of higher humidity and milder temperatures. Our data suggest that there is a clinal distribution pattern of genetic variation along the north to south latitudinal gradient of the Atlantic Forest. This clinal variation has a genetic basis in the frequencies of the two genetic groups. This structure does not evidence long-standing historical barriers to gene flow and favors the influence of landscape characteristics on the establishment of populations.